Faktor-Faktor Yang Mempengaruhi Tax Avoidance Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Jurnal Literasi Akuntansi, 2021)
Purpose: This study aims to examine Return On Assets, Leverage, Size, Tax Loss Carryforwards, Institutional Ownership and The Risk Companies to Tax Avoidance.Method: Sampling using purposive sampling method and obtained 15 companies with data processed 80 annual financial statements. This research technique uses multiple linear regression analysis with SPSS 20 test equipment.Finding: Leverage, institutional ownership and company risk affect tax avoidance. Meanwhile, ROA, size, tax loss carryforwards loss have no effect on tax avoidance.Novelty: The variables of return on assets, company size and compensation for fiscal loss have no effect on tax avoidance in basic chemical industrial companies listed on the Indonesia Stock Exchange in 2016-2020. While the variables of leverage, institutional ownership and company risk affect tax avoidance in basic chemical industrial companies listed on the IDX in 2016-2020.
Keywords: Return On Assets; Leverage; Ukuran Perusahaan; Kompensasi Rugi Fiskal; Kepemilikan Institusi; Resiko Perusahaan; Tax Avoidance